Applied linguistics within the linguistic science framework (Eurasian Journal of Philology Science and Education, 2018)
This article deals with the main problems of applied linguistics. Applied problems cannot be solved without preliminary theoretical research leading to the general principles formulation. And obtained results (clearly practical order) can then be used as a starting point for theoretical constructs.The same situation is with the compilation of the language grammar. We can attribute this to applied linguistics (a grammar textbook that will be used for teaching of native or foreign languages) or in fundamental linguistic research; in both cases, both aspects of language learning are closely intertwined, and only the ultimate goal divides them.Applied linguistics is language learning field with a specific applied purpose, which is directly and specifically addressed to the solution of a definite practical problem.The final solution of applied linguistics is the relationship with specific rules and tasks. Scientific research of the language is a long process of diverse research and directions. Usually in scientific research three directions in linguistics are distinguished: applied, theoretical and descriptive. Each direction has its own specific function and specificity.